The Effect of Prayer Voice and Therapeutic Reminders on the Anxiety of Death of Hospitalized Patients in the CCuDepartment - Delnavaz, Parvin; Sadeghi golafshani, Maedeh; Hojjati, Hamid; Hekmatipour, Nafiseh; Rezaee, Solmaz (International Journal of Psychosocial Rehabilitation, 2020)
Anxiety and fear of dying are unpleasant and common experiences in heart disease. People who have religious beliefs and use spiritual approaches to treat have lower anxiety. Prayer and mentioning are two separate methods of spiritual care.Aim: compare two methods of prayer and mention death anxiety in patients hospitalized in CCU Ward Social Security Golestan Hospitals in 1393.Method: An experimental study was performed on prayer groups (n = 30), mention groups (n = 30), and control groups (n = 30). Intervention was performed in prayer and mentioning group, then each three groups were compared. The questionnaire was Temper death anxiety, and the results were analyzed statistically by analysis.Results: Statistical analysis showed a significant difference between three groups; the lowest death anxiety was found in the mentioning group (P